Guidelines for analysis methods and construction engineering of curved and skewed steel girder bridges - White, Donald Woodrow, 1959- (Report (National Cooperative Highway Research Program), 2012)
"TRB's National Cooperative Highway Research Program (NCHRP) Report 725: Guidelines for Analysis Methods and Construction Engineering of Curved and Skewed Steel Girder Bridges offers guidance on the appropriate level of analysis needed to determine the constructability and constructed geometry of curved and skewed steel girder bridges. When appropriate in lieu of a 3D analysis, the guidelines also introduce improvements to 1D and 2D analyses that require little additional computational costs."--Publisher's description.